2021
DOI: 10.1002/app.50976
|View full text |Cite
|
Sign up to set email alerts
|

Polyaniline grafted chitosan/GO‐CNT/Fe3O4 nanocomposite as a superior electrode material for supercapacitor application

Abstract: Developing appropriate stable electroactive electrode materials for supercapacitor application is the challenging issue, which attracts enormous attention in recent decades. In this regard, Fe3O4 nanoparticles are firstly synthesized on chitosan/graphene oxide‐multiwall carbon nanotubes (CS/GM/Fe3O4). Then, polyaniline (PANI) is grafted on it via in situ chemical polymerization and named as CS/GM/Fe3O4/PANI. The as‐prepared nanocomposites are characterized by Field emission scanning electron microscopy, Fourie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 32 publications
(50 reference statements)
0
8
0
Order By: Relevance
“…The CC has no absorption vibration peak and the MoO 3 /CC shows three new peaks, which is the terminal oxygen symmetry stretching mode of MoO, the bridge oxygen asymmetry and symmetry stretching mode of MoOMo are at 990, 876, and 817 cm −1 , respectively 32 . Meanwhile, the PANI/CC also shows some new peaks at 1000–1600 cm −1 , corresponding to PANI (1556 cm −1 for Quinone rings and 1492 cm −1 for Benzene rings) 33 . The peaks of 1305, 1250 cm −1 are attributed to the stretching vibration of CNC and asymmetric stretching vibration of NH 2 +  in the polaron structure, respectively 34 .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The CC has no absorption vibration peak and the MoO 3 /CC shows three new peaks, which is the terminal oxygen symmetry stretching mode of MoO, the bridge oxygen asymmetry and symmetry stretching mode of MoOMo are at 990, 876, and 817 cm −1 , respectively 32 . Meanwhile, the PANI/CC also shows some new peaks at 1000–1600 cm −1 , corresponding to PANI (1556 cm −1 for Quinone rings and 1492 cm −1 for Benzene rings) 33 . The peaks of 1305, 1250 cm −1 are attributed to the stretching vibration of CNC and asymmetric stretching vibration of NH 2 +  in the polaron structure, respectively 34 .…”
Section: Resultsmentioning
confidence: 95%
“…32 Meanwhile, the PANI/CC also shows some new peaks at 1000-1600 cm À1 , corresponding to PANI (1556 cm À1 for Quinone rings and 1492 cm À1 for Benzene rings). 33 The peaks of 1305, 1250 cm À1 are attributed to the stretching vibration of C N C and asymmetric stretching vibration of NH 2 + in the polaron structure, respectively. 34 The PMC-3 has characteristic peaks of both PANI and MoO 3 .…”
Section: Electrochemical Measurementsmentioning
confidence: 99%
“…However, the (2 0 0) diffraction plane of the PANI matrix may be merged with the diffraction plane of the CNTs, or it is considerably diminished due to a decrease in the crystallinity of the PANI matrix 73 . Both PANI/Au@ f ‐SWNTs and PANI/Au@ f ‐MWNTs ternary nanocomposites exhibit the peak of CNTs as well as AuNPs along with the peaks of PANI at 2 θ value of 14.67°, 20.50°, and 25.67° due to (0 1 1), (0 2 0), and (2 0 0) crystal planes of the PANI 1,73,74 . Furthermore, it is concluded that the Au@ f ‐SWNTs and Au@ f ‐MWNTs hybrid nanofillers are effectively incorporated into the PANI matrix.…”
Section: Resultsmentioning
confidence: 99%
“…73 Both PANI/Au@f-SWNTs and PANI/ Au@f-MWNTs ternary nanocomposites exhibit the peak of CNTs as well as AuNPs along with the peaks of PANI at 2θ value of 14.67 , 20.50 , and 25.67 due to (0 1 1), (0 2 0), and (2 0 0) crystal planes of the PANI. 1,73,74 Furthermore, it is concluded that the Au@f-SWNTs and Au@f-MWNTs hybrid nanofillers are effectively incorporated into the PANI matrix.…”
Section: Xrd Analysismentioning
confidence: 96%
“…Additionally, neutral electrolytes may provide a wider potential window than acidic or alkaline electrolytes; hence, SCs that consist of neutral electrolytes are capable of achieving a higher energy density [35,36]. Previous research established the possibility of 0.5 M Na 2 SO 4 solution as a neutral electrolyte for PANI electrodes in SC applications [37,38].…”
Section: Introductionmentioning
confidence: 99%